A New Strategy for Effective Succinic Acid Production by Enterobacter sp. LU1 Using a Medium Based on Crude Glycerol and Whey Permeate - Podleśny, Marcin (Molecules, 2019)
The newly-isolated strain Enterobacter sp. LU1, which has previously been shown to be an effective producer of succinic acid on glycerol with the addition of lactose, was used for further intensive works aimed at improving the production parameters of the said process. The introduction of an initial stage of gentle culture aeration allowed almost 47 g/L of succinic acid to be obtained after 168 h of incubation, which is almost two times faster than the time previously taken to obtain this amount. Furthermore, the replacement of glycerol with crude glycerin and the replacement of lactose with whey permeate allowed the final concentration of succinic acid to be increased to 54 g/L. Considering the high content of yeast extract (YE) in the culture medium, tests were also performed with a reduced YE content via its partial substitution with urea. Although this substitution led to a deterioration of the kinetic parameters of the production process, using the fed-batch strategy, it allowed a succinic acid concentration of 69 g/L to be obtained in the culture medium, the highest concentration ever achieved using this process. Furthermore, the use of microaerophilic conditions meant that the addition of lactose to the medium was not required, with 37 g/L of succinic acid being produced on crude glycerol alone.